Contrast-enhanced ultrasonography (CEUS) reveals active bleeding into an abdominal hematoma in a patient with ongoing subcutaneous injections - Klenk, Christopher; Clevert, Dirk-André (Zeitschrift für Gastroenterologie, 2022)
A 95-year-old woman with metastasizing bronchial carcinoma presents with left inguinal pain. The referring physician would like to exclude an inguinal hernia and a deep vein thrombosis due to her precondition of essential thrombocythemia. Conventional ultrasound excluded the presence of a deep vein thrombosis yet showed a 6 cm × 5 cm hematoma distal of the left m. rectus abdominis. The subsequently performed color Doppler examination excluded a pseudoaneurysm but could not preclude active bleeding. Eventually, CEUS showed contrast-pooling within the hematoma as a sign of active extravasation, suggesting ongoing bleeding.
Keywords: CEUS; Hämatom; Blutung